2023
DOI: 10.1029/2022jd038124
|View full text |Cite
|
Sign up to set email alerts
|

How a Stable Greenhouse Effect on Earth Is Maintained Under Global Warming

Abstract: As a measure of habitability, the temperature of a planet is determined by the energy balance between the absorption of sunlight and the loss of thermal heat to space. Earth has been habitable for three or 4 billion years (Lepot et al., 2008;Nutman et al., 2016), owing to a relatively stable energy balance.The thermal cooling to space is modulated by gases that are radiatively active in the longwave (thermal) spectra via the greenhouse effect. Simpson (1928) formulated a simple model to explain thermal cooling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 54 publications
5
11
0
Order By: Relevance
“…Interestingly, these positive non-cloud biases tend to be compensated by cloud biases of an opposite sign, which in some models results in a seemingly good all-sky radiation budget (see Table 1 and Table S1 in Supporting Information S1) as noted above. In addition, it is also interesting to notice that the surface temperature caused radiation biases are mostly noticeable in the Polar region, in agreement with the recognition that the atmosphere is the most transparent to surface emission in these regions (e.g., Feng et al, 2023;H. Huang & Huang, 2022).…”
Section: Tablesupporting
confidence: 76%
“…Interestingly, these positive non-cloud biases tend to be compensated by cloud biases of an opposite sign, which in some models results in a seemingly good all-sky radiation budget (see Table 1 and Table S1 in Supporting Information S1) as noted above. In addition, it is also interesting to notice that the surface temperature caused radiation biases are mostly noticeable in the Polar region, in agreement with the recognition that the atmosphere is the most transparent to surface emission in these regions (e.g., Feng et al, 2023;H. Huang & Huang, 2022).…”
Section: Tablesupporting
confidence: 76%
“…When compared to the observed clearsky OLR-T s slope, however, Tcs δB(T s ) is significantly lower and decreases further with increasing T s . The magnitude of Tcs δB(T s ) is highly consistent with the line-by-line calculations conducted in [19] and the clear-sky surface temperature kernel available in publicly accessible datasets [10,20].…”
Section: The Olr-t S Relationship In the Present-day Earthsupporting
confidence: 82%
“…The surface contribution, TδB(T s ), represents the change in OLR resulting from a one-sided partial radiative perturbation in T s . When δT s = 1 K, this term is known as the 'surface Planck feedback' [2,18,19] or the surface temperature kernel [10,20,21] at local grid points. The atmospheric contribution, B(T s + δT s )δ T + δE, accounts for changes in δOLR due to perturbations in atmospheric transmittance and emission.…”
Section: The Olr-t S Relationship In the Present-day Earthmentioning
confidence: 99%
“…More recently, Jeevanjee et al. (2021) explicitly showed that Ingram's result is naturally captured when computing climate feedbacks with relative humidity held fixed, though other studies have emphasized that the outgoing flux is not perfectly constant with surface warming in water vapor bands due to narrowing of water vapor lines and foreign broadening effects (Feng et al., 2023; Raghuraman et al., 2019). Accounting for stratospheric masking slightly revises Ingram's rule: any spectral regions that are not optically thick either to water vapor or in the stratosphere will to first‐order show a “Planckian” increase in flux with warming.…”
Section: Discussionmentioning
confidence: 99%
“…Ingram (2010), highlighting the seminal work of Simpson (1928), clarified that spectral regions where water vapor makes the atmosphere optically thick show nearly zero change in outgoing infrared flux with warming (at constant relative humidity), while all other wavenumbers will show a "Planckian" increase in flux with warming (following 𝐴𝐴 𝐴𝐴𝐴𝐴 𝜈𝜈 ( 𝑇𝑇 𝜈𝜈 𝑏𝑏 ) ∕𝐴𝐴𝑇𝑇 ). More recently, Jeevanjee et al (2021) explicitly showed that Ingram's result is naturally captured when computing climate feedbacks with relative humidity held fixed, though other studies have emphasized that the outgoing flux is not perfectly constant with surface warming in water vapor bands due to narrowing of water vapor lines and foreign broadening effects (Feng et al, 2023;Raghuraman et al, 2019). Accounting for stratospheric masking slightly revises Ingram's rule: any spectral regions that are not optically thick either to water vapor or in the stratosphere will to first-order show a "Planckian" increase in flux with warming.…”
Section: Discussionmentioning
confidence: 99%